Prediction of Rutting in Flexible Pavements using Finite Element Method - Asim, Muhammad; Ahmad, Mahmood; Alam, Muhammad; Ullah, Shahid; Iqbal, Muhammad Junaid; Ali, Shahid (Civil Engineering Journal, 2021)
In this research study three dimensional (3D) finite element analysis are performed on a flexible pavement section for different material properties, temperature and loading conditions. The main objective of this study is to predict the rut depth under different conditions of temperature, loadings and material properties. Three dimensional finite element model of flexible pavement is developed using ABAQUS to predict rut depth. The pavement system is assumed to be an elastic multi-layers system with each layer being isotropic, homogeneous with specified Resilient Modulus (Mr) and Poisson ratio (Âµ). With the exception of the bottom subgrade layer, each layer is extending to an unlimited horizontal extent and has a finite thickness. The pavement system analyze in this study for a cyclic load of 10000 cycles taken as 0.01sec per cycle. Standard Axle Load (ESAL) of 18 kips (80 kN) loading on an axle with a dual set of tires, the wheel spacing is 13.78 in (350 mm) with a tire contact pressure of 100 psi (0.69 MPa) is used. After performing a series of analysis the results showed that rut depth increases with increase in temperature and loading and decreases by using base stabilizer.Â Doi: 10.28991/cej-2021-03091727 Full Text: PDF